Contribuição dos laboratórios farmacêuticos públicos na política de aquisição de medicamentos do Ministério da Saúde - Wenderson Walla Andrade (2014)
INTRODUCTION: Public Pharmaceutical Laboratories (PL) are recognized by the production of medicines for Primary Health Care, given preferably acquisition needs to the state health departments. On the other hand, Private PL are the main suppliers for the Brazilian Medicare System (SUS) as it concerns about medications of high economic and technological value. Faced with this reality, the Federal Government ofBrazil has adopted policies to encourage the growth of the pharmaceutical industry, by increasing investment in Public (PL) in order to expand production and technological capacity of these, reducing costs of centralized purchasing of medicines. For this reason, it was created a Program to Support the Development of the Productive Pharmaceutical Chain (Profarma) and the Partnership for the Productive Development (PDP). OBJECTIVE: To analyze the result of the Policy adopted by the Federal Government for the national pharmaceutical productive sector based on participation of both Public and Private PL in centralized purchasing of medicines made by the Ministry of Health and in the analysis of PDP. MATERIAL AND METHOD: temporal Analysis of financial and physical quantitative of medicines purchases held centrally by the Ministry of Health during the period of 2000 to 2012 and analysis of medicines objects of PDP approved in the period between 2009 and2012 in relation to the location component of pharmaceutical care (PC) and the import of the same to meet the domestic market. The data were obtained from the following sources: Departamento de Assistência Farmacêutica/MS, página da Secretaria de Ciência e Tecnologia e Insumos Estratégicos/MS e portal da transparência do Governo Federal e da Agência Nacional de Vigilância Sanitária (Department of Pharmaceutical Assistance/ Ministry of Health, the Department ofScience and Technology and Strategic webpage/ Ministry of Health and the transparency of the Federal Government and the National Health Surveillance Agency website). They were organized from the expenses and pharmaceutical units (PU) acquired by Ministry of Health by type of supplier and component of PC, with the participation of suppliers in expenses and PU acquired by Ministry of Health in each component of the PC and the number of active substances and items purchased each year. The analyzes were performed by frequencies and average number of PU, the values paid, number of active substances and purchased items.We also analyzed the PDP approved, in which component of PC their medicines make part, the place of manufacture as soon as approval and their results in medicines delivered to Ministry of Health. RESULTS AND DISCUSSION: During the period, the expenses of Ministry of Health with medicines raised 156%, resulting in an increase of 240% in total of PU acquired. Private Pharmaceutical Laboratorieswere the main suppliers, both in relation to the expense and in terms of the number of PU in strategic components (CESAF) and specialized (CEAF) of PC, while the Public ones were the main suppliers of PU in basic component (CBAF). It was observed that of the 46 medicines of PDP approved in period two (4.3%) are not part of any component of PC, 33 (71.8%) are part of the CEAF, being six biological, and 11 (23.9%) part of CESAF. It was also found that 41 of the medicines were imported(89.1%) at the time of PDP approval. It was observed that 10.8% of PDP approved by Ministry of Health resulted in medicines delivered by 2012, providing an increase in the participation of Public PL on Ministry of Health expenses with medicines of CESAF and CEAF and an economy of R$ 140.000.000 (about U$ 70 million in a year) for the Ministry of Health. CONCLUSION: The Public Pharmaceutical Laboratories have complied with the guidelines and objectives of federal programs to the extent that they have prioritized in PDP drugs of high added value, among thembiological medicinal products and medicinal products which were not manufactured in Brazil at the time of the approval by the Ministry of Health. It is important to emphasize that the Public PL have increased its participation in centralized purchasing of Ministry of Health from 2010, mainly in specialized components and strategic of PC (Pharmaceutical Care).